The effect of instructional program by using gymnastic of games in development some of physical abilities and basic motor skills and social growth for children kindergarten - Saleh, Shirwan (Journal of Physical Education, 2016)
The research aims to:1. Prepare a suggested instructional program by using gymnastic of games .2.Knowing the effect of the suggested instructional program by using gymnastic of games in development some of physical abilities and motor skills and social growth for children at kindergarten.The research was conducted on a sample had been selected randomly in age(5) years (male) for primer class and for school year 2010-2011 which reached (30) child that they were divided in single and a double by (15) child for each group.Design was chosen which called "equivalent groups design random selection with pre and posttests".The main experiment implementation has already started on Saturday 7/3/2011 until 18/5/2011 in two educational unit per week, the researchers used the statistical methods: arithmetic mean and standard deviation, the percentage and coefficient of sprains and (t) test has been used.The researchers concluded follows:..1.The results that excrete in pre and posttests proved validity of instructional program by using games of gymnastics through the noticeable development in all physical abilities and basic motor skills under study and social growth.2.Achieved the approach taken in kindergarten (a variety of motion activities) relatively evolution in two skills (front rolling and long jump) as well as social growth while this program did not achieve development in the skills (hung up, walking balance, hope , running winding, running straight and fast walking) in the measurement of pre and posttest.3.Superiority of experimental group children who applied to them the proposed program by using games of gymnastics in measuring a posttest on the control group children who applied to them the program followed (a variety of motion activities) in all physical abilities and basic motor skills and social growth, except skill the (hope), where shares of both two program in the ratio of evolution itself.